'Taking back control’: the ambiguous impact of populist trade discourses on the international economic order - Brusenbauch-Meislova, Monika; Chryssogelos, Angelos (Oxford University Press and Chatham House, 2024)
The relationship between populism and free trade has historically been a complex one. This article argues that populism affects trade not by expressing consistent economic preferences, but by operating as a discourse that articulates external policies as a struggle for popular recognition. We analyze trade discourses of Donald Trump and Brexiteers following their victories in the 2016 US presidential election and the EU referendum in the UK. These populist movements expressed opposing trade preferences: Trumpism was identified with protectionism, while Brexiteers supported free trade. However, they both articulated trade as a way to regain popular sovereignty from elites and hostile outsiders. A discursive approach helps identify a common logic in how populists articulate foreign relations despite pursuing nominally opposing policies. While this populist logic pertains primarily to domestic mobilization, it has implications for the international order as well, as evidenced in the persistence of protectionist instincts in the US under President Biden and the acceptance of a ‘global’ trade policy outside of the EU as the new frame of reference for UK external economic relations.